A short appraisal of nanodiamonds in drug delivery and targeting: recent advancements - Singh, Dilpreet; Ray, Supriya (Frontiers in Nanotechnology, 2023)
Nanodiamonds have emerged as a powerful tool in the field of drug delivery, offering exciting recent advancements and promising future prospects. Recent research has focused on enhancing drug loading efficiency, targeted delivery, and precision medicine using nanodiamonds.Strategies such as surface functionalization, polymer coatings, and encapsulation techniques have been optimized to improve drug loading, stability, and controlled release. Nanodiamonds have shown potential in targeted drug delivery through the incorporation of targeting ligands, enabling site-specific drug delivery and improved therapeutic outcomes. Additionally, nanodiamonds allow for combination therapy by carrying multiple drugs simultaneously, opening avenues for synergistic treatments. Stimuli-responsive nanodiamonds have been developed for precise and controlled drug release. Overcoming biological barriers, such as the blood-brain barrier, has been investigated by modifying nanodiamonds' surfaces. Recent studies have highlighted innovative strategies for loading a variety of therapeutic cargoes onto nanodiamond platforms, including small molecules, proteins, nucleic acids, and even geneediting tools. Future prospects include the integration of nanodiamonds with emerging technologies and addressing biocompatibility and safety concerns. Despite the need for further research and clinical studies, the recent advancements and future prospects of nanodiamonds in drug delivery suggest their potential to revolutionize the field and enhance patient care.